1995
DOI: 10.1099/13500872-141-9-2165
|View full text |Cite
|
Sign up to set email alerts
|

IS1500, an IS3-like element from Leptospira interrogans

Abstract: Copies of an insertion-sequence (IS)-like element were isolated from two closely related serovars of Leptospira intemogans sensu stricto. Nucleotide sequence analysis of the 1236 bp element showed a characteristic IS structure with terminal imperfect inverted repeats (IRs) flanking a 1159 bp central region. This element was designated 151500. Four open reading frames (orfA-orfD) were found in the central 'unique' region of 151500. Similarities were detected between ORFA and ORFB and the putative transposases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
(26 reference statements)
3
23
1
Order By: Relevance
“…Bacterial ISs generate diversity in prokaryotic genomes through proliferation and movement from one insertion site to another. Our analysis of the Copenhageni and Lai genomes revealed the presence of the previously described IS elements IS1500, IS1501, IS1502, and IS1533 (3,5,51) and identified a new IS we designated ISlin1. The number and distribution of IS1501 and ISlin1 differed dramatically, highlighting the impact these elements have in Leptospira species strain genome differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial ISs generate diversity in prokaryotic genomes through proliferation and movement from one insertion site to another. Our analysis of the Copenhageni and Lai genomes revealed the presence of the previously described IS elements IS1500, IS1501, IS1502, and IS1533 (3,5,51) and identified a new IS we designated ISlin1. The number and distribution of IS1501 and ISlin1 differed dramatically, highlighting the impact these elements have in Leptospira species strain genome differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Of the previously described IS elements in Leptospira species, only IS1501 (gi2961088) is found as a completely conserved unit. This element has been reported to be able to transpose, as judged by the heterogeneity in copy number detected among different strains of L. interrogans (3). Differences in IS1501 genomic position and copy number in the two serovars reinforce its transposition activity, as serovar Copenhageni contains five copies found exclusively in CI, while serovar Lai presents three, one copy located in CI and two copies located in CII (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of the L. interrogans genome revealed the presence of the previously described insertion sequence (IS) elements IS1500, IS1501 (58), reminiscent insertions of IS1533 (59) and IS1502 (60) and an IS recently identified that we designated ISlin1 (5) ( Table 2). IS1500, IS1501 and ISlin1 account for 24 insertions distributed throughout chromosome I.…”
Section: Comparative Genomics and Insertion Sequencesmentioning
confidence: 99%
“…It is an essential enzyme for replication and transcription [16]. The region of the L. interrogans genome surrounding gyrA shows evidence of rearrangement [6,7]. To determine the organization of L. interrogans genes £anking gyrA, a series of walking steps were employed to amplify contiguous regions of the genome (Fig.…”
Section: Cloning and Sequencing The L Interrogans Serovar Pomona Gyrmentioning
confidence: 99%
“…Frequent rearrangements in the larger replicon have contributed to novel patterns of rRNA gene organization in L. interrogans [5,6]. DNA rearrangements also occur among L. interrogans serovars, and may involve recombination between homologous copies of repeated DNA sequences distributed throughout the genome [7].…”
Section: Introductionmentioning
confidence: 99%